Enhancing design process efficiency with ergo-aesthetic characteristic through design quality, visual assessment and cultural behaviour of young designers - Zainal Abdullah, Muhamad Ezran (2020)
The industrial designer plays a vital role within the consumerism cycle by making a new technology or an item a pleasure to be owned. The joy of owning an item lies inside the aesthetic and ergonomic principle where the user's preferences have been placed as a priority. The basis of this study is seeing the current practices among Malaysians who specialize in the design field, implementing ergonomic and aesthetic principles. The synergy between these two principles through design quality, visual assessment, and the cultural behaviour criteria has been named as the ergo-aesthetic. In general, the concept of ergo-aesthetic discloses the equilibrium of human behavioral character with form, shape, and symbolism inside a designed product. The coaction between these two aspects, ergonomic and aesthetic, can facilitate optimizing the efficiency of the design process, which contributes to higher output quality. Furthermore, the discrepancy between the users and the object may lead to an unpleasant effect, especially towards the user. Using a non-probability purposive sampling survey, data from 603 respondents have been obtained throughout 32 institutions and firms that practice design-related activities, with 562 respondents who are fit to be analyzed based on a specific underlined criterion. This research is a perfect reflection of young Malaysian designers on their practice throughout the design process based on the positive demographic tendency towards young designers. A general overview of Malaysian young designers' preference on the design process, ergonomic domain, and aesthetic domain during the design development process has been organized accordingly, i.e. towards the design quality, visual assessment, and cultural behaviour. This tabulation on the designer's preference contributes to the development of a new design framework consisting of the enhanced aspect by highlighting the most vital element in a design process. The finding has shown that there is a significant relationship between ergonomic and aesthetic attributes. Thus, an ergo-aesthetic framework has been generated based on the designer's preferences level to assist the designers in the earlier stage of the design processes. The major findings of this research show each of ergo-aesthetic element are exclusively connected, and the priority levels inside the ergo-aesthetic framework assist designer determine the essential elements that are important while designing. Thus, this research has shown that ergonomic, and aesthetic are related to each other, which then contribute towards the design process enhancement through design quality, visual assessment and cultural behaviour element. In this context, ergo-aesthetic principles replace the traditional method of evaluating and adapting ergonomic and aesthetic into the design process to achieve a better output product.